(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Starting an analysis of metaphysical grounds social knowledge is necessary to decide on categorical apparatus, having considered in interconnection, first of all the category of general and history. By the middle of the 19th century, finally formed the question of what constitutes social life and what is its nature if determine the latter without going beyond most public life and historical reality. All this lets talk about shaping sociology as a process of developmentally related to the whole complex co-humanities disciplines.